2013
DOI: 10.1002/pd.4126
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal plasma DNA fetal fraction on next generation sequencing tests for common fetal aneuploidies

Abstract: Maternal plasma contains circulating cell-free DNA fragments originating from both the mother and the placenta. The proportion derived from the placenta is known as the fetal fraction. When measured between 10 and 20 gestational weeks, the average fetal fraction in the maternal plasma is 10% to 15% but can range from under 3% to over 30%. Screening performance using next-generation sequencing of circulating cell-free DNA is better with increasing fetal fraction and, generally, samples whose values are less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
314
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(332 citation statements)
references
References 18 publications
10
314
0
5
Order By: Relevance
“…More recently, cell-free fetal (cff ) DNA in maternal plasma has been used to screen for fetal aneuploidies (Song et al 2013;Bianchi et al 2014). Maternal blood contains both fetal and maternal cell-free nucleic acids, but the fetal contribution to plasma cellfree DNA is a minority (Canick et al 2013;Rava et al 2014). To examine pure fetal nucleic acids, therefore, fetal sources such as chorionic villi, placenta or amniotic fluid (AF) must be obtained through a diagnostic procedure.…”
mentioning
confidence: 99%
“…More recently, cell-free fetal (cff ) DNA in maternal plasma has been used to screen for fetal aneuploidies (Song et al 2013;Bianchi et al 2014). Maternal blood contains both fetal and maternal cell-free nucleic acids, but the fetal contribution to plasma cellfree DNA is a minority (Canick et al 2013;Rava et al 2014). To examine pure fetal nucleic acids, therefore, fetal sources such as chorionic villi, placenta or amniotic fluid (AF) must be obtained through a diagnostic procedure.…”
mentioning
confidence: 99%
“…Both agree with earlier studies. 2,13 Gestational age accounts for 4.2% variation of log fetal fraction and maternal weight accounts for 13.9%, and combined they account for 15.4%.…”
Section: Fetal Fractionsmentioning
confidence: 99%
“…Multiple studies have pointed out that the fetal fraction plays a crucial role in the effectiveness of NIPS to detect trisomy. [13][14][15][16] The consensus for the detecting limit of the fetal fraction appears to be 4%, although theoretical studies have suggested that 2% also works, 14 and more optimistic authors have suggested that as long as GC bias is accounted for and sequence depth is unlimited, NIPS can be effective for an arbitrarily small fraction of fetal DNA. 17 The prevailing method used to analyze NIPS data sets, first outlined in ref.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,11,12 Fetal fraction results, and z-scores in Down syndrome pregnancies, were subjected to a logarithm transformation before comparison, as these data are right skewed. 13 Proportions were compared using Fisher's exact tests. Significance was two tailed at P < 0.05; no adjustment for multiple comparisons was made.…”
Section: Brief Reportmentioning
confidence: 99%